2022
DOI: 10.3390/foods11182869
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Changes in Proteins Caused by High-Pressure Homogenization Promote Nanoparticle Formation in Natural Bone Aqueous Suspension

Abstract: As a natural calcium resource, animal bone needs to be miniaturized to the nanoscale to improve palatability and absorption capacity. To explore the mechanism of high-pressure homogenization (HPH) in preparing natural bone aqueous nanosuspensions, the relationships between the changes in protein conformation, solubility and quality characteristics of rabbit bone aqueous suspensions (RBAS) prepared by different HPH cycles were studied. The results showed that the improvements in particle size, stability and cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Opposite this, Val and Ile are non-polar with long carbon chains; consequently, they are hydrophobic. UHP strongly modifies the structure of water, which allows exposure of the non-polar surface to water and eventually completely stops hydrophobic interactions resulting in the reorganization of amino acid residues in peptide chains [52]. SEM microscopy showed that 400 MPa for 10 min did not evoke significant changes in configuration and ordering over longer distances than the original collagenous gel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Opposite this, Val and Ile are non-polar with long carbon chains; consequently, they are hydrophobic. UHP strongly modifies the structure of water, which allows exposure of the non-polar surface to water and eventually completely stops hydrophobic interactions resulting in the reorganization of amino acid residues in peptide chains [52]. SEM microscopy showed that 400 MPa for 10 min did not evoke significant changes in configuration and ordering over longer distances than the original collagenous gel.…”
Section: Discussionmentioning
confidence: 99%
“…The side chains of Glu and Asp have carboxylic acid groups whose pKas are low enough to lose protons, becoming negatively charged. Appropriate amounts of UHP cycling can disrupt hydrogen bonds, ionic bonds, and disulfide bonds [52]. Opposite this, Val and Ile are non-polar with long carbon chains; consequently, they are hydrophobic.…”
Section: Discussionmentioning
confidence: 99%
“…High-pressure homogenization (HPH) is a non-thermal physical process for reducing the particle size of a sample (emulsion or suspension) from the micron range to the nanometer range by using shear, impact and cavitation effects at high pressure [ 22 ]. Due to its high production efficiency and stability, HPH has been widely used to produce emulsions [ 23 ], nanosuspensions [ 24 ], liposomes [ 25 ], etc. However, few studies have focused on the application of HPH to produce Pickering nanoemulsions.…”
Section: Introductionmentioning
confidence: 99%